Approximate analytical method for prediction of performance and optimum dimensions of pin fins subject to condensation of quiescent vapor - Kundu, B. (International journal of refrigeration, 2009)
An approximate analytic method is proposed to solve the governing equation of horizontal pin fins subject to the condensation of saturated vapor under laminar free convection. The temperature distribution and performance parameters are determined by using Adomian decomposition method. A numerical scheme followed by the finite difference method has been used to validate the present analytical result. From the results, a significant effect on the temperature distribution and performances with the variation of fin dimensions and thermophysical parameters of saturated vapor is noticed. Next, a scheme for fin optimization has been carried out in such a way that either heat transfer duty or fin volume can be taken as a constraint selected according to the requirement of a design. Finally, dependency of design variables on an optimum condition has been established which may help the designer to adopt physical conditions in a practical application.